(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the beginning of the creation, there appears to be no restraint on any plant or animal and survival through careful and diligent movements suitable to the creature being considered to be a part of life. In due course of time, under cultural canopy, some plants and animals have been chosen to be preferable for food and some discarded basing on their nature and characteristics. When man’s wisdom started growing, many agencies and institutions like religion and politics started exercising control over the food items, be it vegan or meat-related, for human consumption. Religious regulation is found to be rigorous when compared with the political intervention, and any use of food item declared to be unlawful by the religious belief becomes a taboo. Restrictions on specified food items results in total annihilation or stoppage of production. Thus food production becomes permissible only in respect of the so-called lawful items declared legal and accepted by public.